This Economy Kills : Pope Francis on Capitalism and Social Justice - Tornielli, Andrea, 1964-; Galeazzi, Giacomo (Book collections on Project MUSE., 2015)
When Pope Francis wrote in his apostolic letter The Joy of the Gospel that the economy of the West is one that "kills," he was immediately labeled by some as a Marxist. Criticisms came fast and furious, not only from financial columnists and conservative cable personalities, but also from some Catholic commentators, especially in the United States. In This Economy Kills, two of the most respected journalists covering the Vatican today explore the Pope's teaching and witness on the topic; the ways it relates to other topics like war, the environment, and family life; its connections to the teaching of his predecessors; and the criticism it has generated, especially from the direction of the United States. This fascinating book includes the full text of an extended interview the authors conducted with Francis on the topic of capitalism and social justice, appearing here in English for the first time. This Economy Kills is essential reading for anyone who wants to understand Pope Francis's convictions about the world we live in and the way he believes Christians are called to shape it.